MATHEMATICAL MODELING AND SIMULATION OF THE PREHEATING ZONE OF A TUNNEL KILN - (:unkn) unknown (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2011)
Simulation of drying bricks in the preheating zone of a tunnel kiln was done by developing a one dimensional model describing the gas flow, heat transfer between gas and bricks and evaporation of bound water. Simulation results were compared to the previously measured plant data. Ambient air was fed into the preheating zone using two different profiles and vent locations to achieve desired gas temperature for high quality bricks. Temperature profiles obtained using both approaches agreed well with measurements. When no ambient air is fed, gas temperature was shown to reach 350 degrees C at the preheating zone entrance which is not desired for the best quality product. Bound water in the bricks, which should be evaporated completely, approaches zero while reaching the 70% of the dimensionless length of the preheating zone.
Keywords: Tunnel kiln; Preheating zone simulation; Evaporation of bound water; Gas temperature profile; CONVECTIVE HEAT-TRANSFER; OPTIMIZATION; BRICKS; FUEL; AIR